The Effect of Faecal Sludge Biochar on the Growth and Yield of Tomato (Solanum lycopersicum L.) Cultivar Micro-Tom - H. Larissa Nicholas; Aisling Devine; Iain Robertson; Ian Mabbett (Agronomy, 2023)
Full-scale pyrolysis of faecal sludge in developing nations is an emerging technology for the complete removal of pathogens and the concurrent creation of biochar, a soil amendment shown to enhance crop productivity. Currently there is little information on the effects of faecal sludge biochar on soil and crop yield. Faecal sludge biochar was applied to an acidic, sandy soil to assess its effects on plant growth and yield in Micro-Tom, a model cultivar of tomato (Solanum lycopersicum L.). We examined four soil application treatments: a control soil, fertilizer treatment, biochar treatment, and a combined biochar and fertilizer treatment. The combined treatment of biochar and fertilizer together produced a tomato yield 2980% greater than the tomato yield from control soil, whereas biochar on its own increased the yield by 1060%. There was no significant difference in plant height between the combined biochar and fertilizer application and biochar on its own; however, both treatments significantly increased plant height compared to control soil. Below ground biomass showed a similar pattern, with no significant difference between biochar alone and combined biochar and fertilizer treatments, and both treatments resulted in significantly increased below ground biomass compared to control soil. The combined biochar and fertilizer treatment resulted in significantly lower water runoff than all other treatments. These findings have great potential implications for increasing food security and the creation of more sustainable agricultural practices, especially in developing regions.